Flipside of the Coin: Iron Deficiency and Colorectal Cancer - Aksan, Aysegül; Farrag, Karima; Aksan, Sami; Schroeder, Oliver; Stein, Jürgen (Frontiers in Immunology, 2021)
Iron deficiency, with or without anaemia, is the most frequent haematological manifestation in individuals with cancer, and especially in patients with colorectal cancer. Iron is a vital micronutrient that plays an essential role in many biological functions, in the context of which it has been found to be intimately linked to cancer biology. To date, however, whereas a large number of studies have comprehensively investigated and reviewed the effects of excess iron on cancer initiation and progression, potential interrelations of iron deficiency with cancer have been largely neglected and are not well defined. Emerging evidence indicates that reduced iron intake and low systemic iron levels are associated with the pathogenesis of colorectal cancer, suggesting that optimal iron intake must be carefully balanced to avoid both iron deficiency and iron excess. Since iron is vital in the maintenance of immunological functions, insufficient iron availability may enhance oncogenicity by impairing immunosurveillance for neoplastic changes and potentially altering the tumour immune microenvironment. Data from clinical studies support these concepts, showing that iron deficiency is associated with inferior outcomes and reduced response to therapy in patients with colorectal cancer. Here, we elucidate cancer-related effects of iron deficiency, examine preclinical and clinical evidence of its role in tumourigenesis, cancer progression and treatment response. and highlight the importance of adequate iron supplementation to limit these outcomes.